(untitled) (Research, Society and Development, 2021)
Candida spp. are yeasts present in the microbiota of humans and animals, but due to disorders, they can become pathogenic, causing candidiasis. This study aimed to evaluate the diversity of Candida species in domestic and wild animals and the antifungal susceptibility profile. A total of 79 isolates were obtained from domestic animals (n=49) and wild animals (n=30) collected from 13 different injury sites. The isolates were previously characterized morphologically and tinctorial and the definitive classification occurred by DNA sequencing of the ITS region. The broth microdilution technique obtained the susceptibility profile with the antifungal agents: caspofungin, fluconazole, voriconazole, amphotericin B, nystatin, and itraconazole. Twelve different Candida species were identified, where C. rugosa was the most isolated species (26%, 21/79), followed by C. parapsilosis (20%, 16/79) and C. albicans (15%, 12/79). The susceptibility profile was evaluated in 30 isolates (10 isolates of C. glabrata, ten of C. tropicalis, and ten of C. parapsilosis), resulting in 100% of the tested isolates being resistant to itraconazole. Still, none of them was resistant to voriconazole. Isolates of C. tropicalis were resistant to multiple antifungal agents. These data alerted the worldwide problem of antimicrobial resistance, aggravated by the emergence of strains resistant to multiple drugs. This study is the first study that verified the occurrence and resistance profiles of Candida spp. in animals in Mato Grosso State, Midwest, Brazil, encouraging the execution of new works further to understand the relationship between these yeasts and their hosts.